Síntese e caracterização de nanofibras de zeína incorporadas com progesterona e medroxiprogesterona. - Santos, Camila de Oliveira (2015)
It is estimated that the economic potential of nanofibers is now worth $ 14 billion, but exploiting this potential depends directly on the development of new techniques so that fibers are obtained with lower cost and higher efficiency. Given this scenario, the objective of the study was to obtain zein fibers with nano and micrometer diameter with the aid of an electrospinning system and meet the physicochemical properties of the fibers. The zein is a protein from corn and contains various types of amino acid residues. The electrospinning system is the most widely used systems for obtaining nanofibers. An ethanol / water system was used to assess the addition of a nonsolvent to the biopolymer. Pure fibers were evaluated and fibers containing progesterone (P4) and medroxyprogesterone (MP4). The morphology of the fibers was investigated by scanning electron microscopy (MEV) as a function of several variables such as concentration of biopolymer in solution, solvent and nonsolvent. A systematic study of these variables was obtained and the quantitative relationship between these parameters and the mean diameter and standard deviation of fibers has been established. The obtained nanofibers were characterized by various analytical steps, and the effect of the presence of progesterone and medroxyprogesterone on the morphology, thermal and crystallographic properties was determined. The results indicate the possibility of controlling the morphology of the fibers through the control solution variables (concentration of biopolymer, solvent and presence of non-solvent). The addition of water as non-solvent produced more homogeneous fiber, studies have shown that different parameters directly influence the production of the fibers. Morphological analysis showed that the measure which increases the amount of hormone also increases the presence of beads in the structure thereof. In conclusion queo system has great potential for the production of controlled release systems.